Monday

December 22, 2014

December 22, 2014

Posted by **Lauryn** on Wednesday, November 21, 2012 at 8:34pm.

- Algebra -
**Henry**, Friday, November 23, 2012 at 3:58pmLog2(8x^2+48x+72).

Log2(8)(x^2+6x+9) =

Log2(8)(x+3)^2 =

Log2(8)+2Log2(x+3) =

3 + 2Log2(x+3).

**Answer this Question**

**Related Questions**

Algebra - Find the product: -6x(-8x^2+x+5) A)-14x^3-5x^2-x B)48x^3+x+5 C)48x^3-...

math - solve the equation log2(x+4)-log4x=2 the 2 and 4 are lower than the g ...

Algebra 2 - solve log2(3x-1)-log2(x-1)=log2(x+1) i have absolutely no idea how ...

Logarithms - I'm working on logarithmic equations and I'm stuck on how my book ...

algebra - (48x^6)/(48x^6/12x^2-12y^2)/(4x^5)/(3xy+3y^2)

Algebra II - Solve log2(7x-3)>= log2(x+12) My work: 6x=15 x=15/6 x-5/2 so my ...

algebra - Solve for x 1. log5 X=3 2. Log2 16-log2 =x 3. Log9 6561=x

math/algebra - solve the equation log2(3x-2) - log2 (x-5)=4

Algebra - Solve the logarithmic equation. log2(4x)-log2(x+3)=1

add maths - Given that log2 3=h and log2 5=k, express log2 0.45 in terms of h ...